Racial discrimination, objectalisation and reactive disobjectalisation—Pathways of integration for young Muslims in Germany. (20th December 2022) - Kaiser, Paul Maximilian; Barth, Lena; Tuncel‐Langbehn, Gonca; Ruettner, Barbara; Goetzmann, Lutz
Abstract: This paper aims to investigate the relationship between contending objectalisation, reactive disobjectalisation and radicalization tendencies during the integration of 50 young Muslims in Germany. The largest group of people who have a history of migration in Germany are people of Turkish and Kurdish origin. During the summer and autumn of 2018, we interviewed 50 individuals from both genders aged from 18 to 25 years old. We saw that negative or contending objectalisation could lead to a reactive disobjectalisation of the German world. This reactively results in an increased occupation of Turkish culture, especially religion and radicalization, which focuses the intensification of religious views. As a result of this process, religious behavior intensifies, which is shaped by going to religious groups, mosques and activities in Islamic organizations. There also appears to be some kind of "new national feeling" where objectalisation of both cultures results in a third identity in the form of its own psychic integration. In this way a new migratory identity would be formed which inherits the "best of both cultures."